HUBUNGAN DUKUNGAN KELUARGA DAN PENGETAHUAN DENGAN KEPATUHAN IBU HAMIL DENGAN HIV DALAM MENGKONSUMSI ARV DI RSUD PROF. DR. MARGONO SOEKARJO PURWOKERTO - Anasari, Tri; Trisnawati, Yuli (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2018)
One of the Millennium Development Goals (MDGs), the sixth goal is the fight against HIV / AIDS, malaria and other infectious diseases. The goal of this indicator is to reduce HIV infection by half, including taking antiretroviral treatment measures. Non-adherence of patients to antiretroviral therapy can have a huge negative effect because the percentage of HIV / AIDS disease reaches 54%. The variables affecting compliance are family and knowledge support. The purpose of this study is to analyze the relationship of family support and knowledge with the compliance of pregnant women with HIV in taking antiretrovirals. The type of this research is observational analytic with cross sectional approach. The population is pregnant women with HIV who are taking antiretrovirals. The sample is 35 people and the sampling technique is total sampling. Univariate analysis to describe all research variables by arranging frequency distribution table from each variable. Bivariate analysis using chi square test. The results showed that most pregnant women received family support, good knowledge and adherence to taking antiretrovirals. There is a relationship between family support and knowledge with adherence of pregnant women with HIV in taking ARVs with p-value = 0.011 and 0.005. The conclusion of this study is that there is a significant relationship between family support and knowledge with adherence of pregnant women with HIV in taking antiretrovirals. Keywords: family support, knowledge, adherence, pregnant women, HIV, Antiretroviral